SAXS study of formation and growth of tin oxide nanoparticles in the presence of complexing ligands - Broussous, L.; Santilli, Celso Valentim [UNESP]; Pulcinelli, Sandra Helena [UNESP]; Craievich, A. F. (Amer Chemical Soc, 2002)
The effect of acetylacetone (acac) complexing ligand on the formation and growth of tin oxide-based nanoparticles during thermohydrolysis at 70 degreesC of a tin precursor SnCl4-n(acac)(n) (0 less than or equal to n less than or equal to 2) solution was analyzed by in situ small-angle X-ray scattering. A. transparent and stable sol was obtained after 2 h of thermohydrolysis at 70 degreesC, allowing the quantitative determination of the particle volume distribution function and its variation with the reaction time. The number of colloidal particles for equivalent thermohydrolysis temperature and time decreases as the [acac]/[Sn] ratio in initial solution increases from 0.5 to 6. Instead, the amount of soluble species remaining in solution increases for increasing [acac]/[Sn] ratio within the same range. This indicates that increasing amounts of Sn-acetylacetone complexes partially prevent the hydrolysis and consequent formation of colloidal particles. The N-2 adsorption isotherm characterization of freeze-dried powders demonstrates that the average pore size is approximately equal to the average size (approximate to9 Angstrom) of the colloidal primary particles in the sol, and that the porosity and surface area (approximate to200 m(2) g(-1)) are independent of the acac content in the initial solution.